Acute mesenteric ischemia - Cheng-Cheng SUN; Xue-Liang JIANG (Yixue xinzhi zazhi)
Acute mesenteric ischemia is a group of diseases characterized by disruption of blood supply to different parts of the intestine leading to ischemia and secondary in-flammation. Due to its atypical early symptoms, rapid progression of disease and no specific auxiliary examination, it is often difficult to diagnose and lack of timely treatment, re-sulting in high mortality and poor prognosis. Rapid diagnosis, early intervention for dif-ferent etiologies and multidisciplinary collaboration can significantly improve prognosis. This article summarizes the etiology, anatomical and pathophysiological basis, clinical manifestations, auxiliary examination, and treatment progress of acute mesenteric is-chemia in order to improve the early diagnosis and timely treatment of this serious life-threatening disease.